The Application of Probing Prompting Learning Model to Increase Activity and Mathematics Learning Outcomes - Indayani Wardana Kusuma Wati; Fury Styo Siskawati; Tri Novita Irawati (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2021)
Learning is a key activity of the educational process. Researchers conducted observations in class VII-A MTs As-sunniyah Ranuyoso virgin and approximately 80% of the data obtained shows student scores ≤ 70. This study aimed to determine Increased Activity dan Student Result in studying the math the subject is social arithmetic with probing prompting learning model. Type of research is a classroom action research (CAR). The procedure used is the model cycle based on these result, the percentage of student learning in the first cycle of 60,3%, and a second cycle 0f 92,8%. While the result of daily tests of student in the first cycle obtained average value 31,5, while on the second cycle of 79,95. It is proved that the activity and student learning outcomes can be improved with the implementation of probing prompting learning model. For a particular subject, type probing prompting learning model is used to avoid boredom in learning actifity.   Keywords: probing prompting, learning activity, learning outcomes.